Real-world efficacy and safety of nab-paclitaxel plus gemcitabine-cisplatin in patients with advanced biliary tract cancers: a multicenter retrospective analysis. (August 2021) - Cheon, Jaekyung; Lee, Choong-kun; Sang, Yun Beom; Choi, Hye Jin; Kim, Min Hwan; Ji, Jun Ho; Ko, Kwang Hyun; Kwon, Chang-Il; Kim, Dae Jung; Choi, Sung Hoon; Kim, Chan; Kang, Beodeul; et al.
Background: A recent phase II trial reported prolonged survival in patients with advanced biliary tract cancer (BTC) following treatment with nab-paclitaxel plus gemcitabine-cisplatin (Gem/Cis/nab-P). We aimed to evaluate the clinical outcomes of Gem/Cis/nab-P in Asian patients with advanced BTC in a real-world setting. Methods: We reviewed the data of patients who received Gem/Cis/nab-P for the management of advanced BTC between September 2019 and April 2021 at four institutes in Korea. Patients were classified into the Gem/Cis/nab-P and nab-P addition groups depending on the starting point of nab-P administration. Results: A total of 178 patients treated with Gem/Cis/nab-P were included in the study. Of these, 43.8% had intrahepatic cholangiocarcinoma (CCA), 34.8% had extrahepatic CCA, and 21.3% had gall bladder cancer. A total of 117 (65.7%) patients received Gem/Cis/nab-P as the first-line treatment, while 61 (34.3%) were treated with gemcitabine-cisplatin-based chemotherapy followed by nab-P addition. The objective response rate (ORR) and disease control rate in all patients were 42.1% and 84.8%, respectively. The ORR in the Gem/Cis/nab-P group was 47.9%, while that in the nab-P addition group was 31.1%. The median progression-free survival and overall survival were 8.5 months [95% confidence interval (CI), 6.9–10.1] and 14.6 months (95% CI, 10.2–19.0), respectively. In patients who received Gem/Cis/nab-P as initial treatment, the median PFS was 9.4 months (95% CI, 7.9–10.9) and the median OS was not-reached (95% CI, not available). Anemia ( n = 42, 23.6%), neutropenia ( n = 40, 22.5%), and thrombocytopenia ( n = 16, 9.0%) were the most common grade 3–4 toxicities. A total of 20 patients (11.2%) had conversions from unresectable to resectable disease and underwent surgery with curative intent. Conclusion: Gem/Cis/nab-P showed favorable real-life efficacy and safety outcomes in Korean patients with advanced BTC, which was consistent with the phase II trial outcomes.